Comparative analysis of the usage of Angular2 and Ember.js frameworks - Palak, Jan; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2018)
The focus of this article is the comparative analysis of the usage of the Angular2 and Ember.js frameworks. The requirement for tests of these frameworks has been developed though special web applications. The analysis was performed with the following comparative criteria: the speed of the website generation, presentation of large amount of data, media services, security mechanism, documentation availability, different data format handling, and integration with social media. Also, this paper aims to present common features and differences between the two frameworks regarding their characteristic features.